Coagulopathy complicating intraoperative blood salvage in patients receiving cesarean section: three case reports and a literature review - Yang Zhang; Wei-Rong Gu; Xi-Rong Xiao (IMR Press, 2022)
Background: Intraoperative cell salvage (ICS) has been used in more than 1100 published obstetrics cases and can reduce the need for allogeneic transfusion effectively. However, ICS could lead to a life-threatening coagulopathy called salvaged blood syndrome (SBS). SBS was reported in several non-obstetric cases but has rarely been reported in obstetric patients. Cases: We reviewed all 841 cell savage cases that occurred in our hospital prior to October 2018. Here, we present 3 cases of coagulopathy in patients who received ICS after cesarean section. The rate of obstetrical SBS in our hospital was 0.46%. Dicussion: Cesarean section was performed without severe hemorrhage, and we performed the surgical hemostatic procedures as usual. Then, several hours after the surgery and after ICS, bleeding occurred, in which hypofibrinogenemia was more severe than expected based on the amount of postpartum hemorrhage. In addition, other marked changes in coagulation function-related parameters, including a decline in the platelet count and obvious prolongation of the PT and aPTT levels, were also observed. More specific and in-depth studies concerning obstetric SBS are needed.